A Young Girl with Barely Symptomatic Congenital Mitral Valve Disease (Cardiovascular Journal, 2021)
Congenital mitral valve disease or malformation may be isolated or associated with other cardiac anomalies. Mitral valve may affect its different segments during development. This anomaly is due to mitral valve with a single fibrous annulus with two orifices (Double orifices mitral valve) that open into the left ventricle. It may be associated with stenosis and or mitral regurgitation. Here we describe a 17 years young girl with palpitation and shortness of breath on moderate to severe exertion. Examination of the cardiovascular system, chest including precordium revealed no abnormality. She is acyanotic and there is no clubbing. On Trans thoracic Echocardiogram isolated double orifice mitral valve was found with no other associated congenital anomalies.Cardiovasc j 2021; 14(1): 79-81